Sistem Monitoring Cahaya Dan Suhu Pada Kandang Ayam Broiler Berbasis Internet Of Things - Ramadhoni, Muhammad; Windyasari, Vina Septiana; Djamaludin, Djamaludin (Universitas Islam Syekh Yusuf Tangerang, 2025)
Temperature and lighting conditions in chicken coops greatly affect the health and productivity of livestock. However, many farmers in Indonesia still monitor the coop environment manually, which is inefficient and poses a high risk to chicken health. To address this issue, this study designed an Internet of Things (IoT)-based temperature and light Monitoring system that can automatically and in real-time monitor and control coop conditions. The system uses a NodeMCU ESP8266 microcontroller integrated with a temperature sensor and an LDR light sensor. The collected data is displayed on an LDR screen and sent to the Blynk app on a smartphone, enabling farmers to monitor coop conditions remotely. The system is also equipped with two relays to automatically control fans and lights based on sensor values, as well as a manual control feature that automatically returns to default mode within 1 minute. The development method used is prototyping, with a black-box approach for system Testing. The results of Testing the IoT-based chicken coop light and temperature Monitoring system show that the lights turn on when light intensity is below 20 lux and the fan